À propos de quelques lettres inédites d’Alexandre Louria à Kurt Goldstein - Alexandre Métraux; Stefan Frisch (Philosophia Scientiæ)
The analysis of the circumstances in which Alexander Luria came to send letters to Kurt Goldstein sheds some light on the historical context of their existence. The documents show how strongly Luria and some of his colleagues were interested in Goldstein’s works in the early 1930s. These documents dating from the post Second World War years also testify to the beginning of the more than purely professional relationship between the two recognized neurologists (or neuropsychologists).